2021
DOI: 10.1186/s13036-021-00265-6
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-chitosan core-shell microcapsule cultures of hepatic cells in a small scale stirred bioreactor: impact of shear forces and microcapsule core composition

Abstract: A small scale stirred bioreactor was designed and the effect of different agitation rates (30, 60 and 100 rpm) was investigated on HepG2 cells cultured in alginate-chitosan (AC) core-shell microcapsule in terms of the cell proliferation and liver-specific function. The microencapsulated hepatic cells could proliferate well when they were cultured for 10 days at 30 rpm while the cell-laden microcapsules showed no cell proliferation at 100 rpm in the bioreactor system. Albumin production rate, as an important li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Hepatocytes cultured in different 3D scaffolds of other studies showed similar enhancements in liver-specific activities (Wu et al, 2014;Wang et al, 2019). The improved microencapsulated cell viability outcomes are consistent with the liver-specific function data, suggesting the benefits of the 3D culture system (Khodabakhshaghdam et al, 2021). This indicates that the 3D culture system with a specific hydrogel combination had no cytotoxic effect on cell metabolic activity.…”
Section: Urea Synthesissupporting
confidence: 80%
“…Hepatocytes cultured in different 3D scaffolds of other studies showed similar enhancements in liver-specific activities (Wu et al, 2014;Wang et al, 2019). The improved microencapsulated cell viability outcomes are consistent with the liver-specific function data, suggesting the benefits of the 3D culture system (Khodabakhshaghdam et al, 2021). This indicates that the 3D culture system with a specific hydrogel combination had no cytotoxic effect on cell metabolic activity.…”
Section: Urea Synthesissupporting
confidence: 80%
“…The cells in these systems are typically under sheer stress, allowing a high mass transfer rate to be achieved throughout the cultures [37][38][39]. Bioreactors have been successfully implemented for a variety of cell types, including heart, muscle, liver, embryonic stem cells and mesenchymal stem cells [40][41][42][43][44][45]; while showing great potential in the toxicity testing of potential therapeutic drugs [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…The stir speed and shape of the stirrer allows for significant control over the mass transfer and shear stress in the system. Variation of the stir speed in this manner has been shown to impact the levels of different ECM components secreted by chondrocytes [57] and affect properties such as albumin secretion in HepG2 hepatocellular carcinoma cells [58] . One of the most common uses in tissue engineering is for the expansion of stem cells by maintaining stem cell pluripotency and offering an alternative to methods such as feeder layers [59] , [60] , [61] .…”
Section: Bioreactor Design and Usagementioning
confidence: 99%